The Efficiency of Various Fire Protectants for Wooden Structures - I.O. Fedotov; A.B. Sivenkov; G.Sh. Khasanova (Eurasian Chemico-Technological Journal, 2022)
The article deals with the scientific problem of the development and application of various fire protective compositions for wooden structures. Based on the results of theoretical and experimental studies, the authors for the first time attempted to state the influence of the chemical nature and mechanism of flame retardant action on the effectiveness of fire protection means. When assessing the effectiveness of fire protection, the authors paid special attention to the key parameters that determine the fire resistance of wooden structures. The possibility of developing effective fire protection systems, capable not only to provide a certain group of fire protection efficiency but also to influence the parameters of the charring process and the intensity of wood heating temperature is shown. Complex mechanisms of bloating (intumescence) and carbonization in combination with the mechanism of regulating the process of carbonization and wood carbonization, are able to provide the protected material with effective resistance to high temperatures (fire). The use of such types of fire protection allows forming an independent scientific direction associated with the development and use of fire protection systems contributing not only to the effective reduction of fire danger of wood and materials based on it but also to increasing the fire resistance of wooden structures.